Наукові основи адаптації мікроклонів і вирощування журавлини в умовах закритого ґрунту - Strila, T.E. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2001)
Scientific grounds of adaptation of microclones from the culture of isolated tissues and growing technologies under the conditions of protected ground have been developed.